2020
DOI: 10.1111/sed.12700
|View full text |Cite
|
Sign up to set email alerts
|

Climatic signals in lacustrine deposits of the Upper Yacoraite Formation, Western Argentina: Evidence from clay minerals, analcime, dolomite and fibrous calcite

Abstract: Authigenic clays are an important control on reservoir quality in lacustrine carbonates but remain challenging to predict. Lacustrine depositional systems respond to climatic variations in rainfall, surface runoff and groundwater input, and evaporation, and result in rapid and frequent changes in lake volume; this is expressed through changing water depth and shoreline position. In the upper portion of the Early Palaeocene Yacoraite Formation of the Salta Basin in Argentina, extensive lacustrine deposits were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 49 publications
2
26
0
Order By: Relevance
“…This interpretation agrees with and reinforces the previous palaeoenvironmental proposal of Cónsole-Gonella et al (2017, 2021. Some authors suggested the presence of stromatolites in lake systems in the southern sector of the basin (Metán-Alemanía sub-basin) (Bunevich et al 2017;Gomes et al 2019;Deschamps et al 2020). Given the size of the basin and its distance from Maimará locality (Tres Cruces sub-basin), it is accepted that this may be correct.…”
Section: C Palaeoenvironmental Modelsupporting
confidence: 90%
See 1 more Smart Citation
“…This interpretation agrees with and reinforces the previous palaeoenvironmental proposal of Cónsole-Gonella et al (2017, 2021. Some authors suggested the presence of stromatolites in lake systems in the southern sector of the basin (Metán-Alemanía sub-basin) (Bunevich et al 2017;Gomes et al 2019;Deschamps et al 2020). Given the size of the basin and its distance from Maimará locality (Tres Cruces sub-basin), it is accepted that this may be correct.…”
Section: C Palaeoenvironmental Modelsupporting
confidence: 90%
“…Over the years, several stromatolite deposits have been recognized from this geological unit, but only mentioned or briefly described and discussed in a regional palaeoenvironmental and sedimentological context (e.g. Marquillas, 1984Marquillas, , 1985Palma, 1984;Marquillas & Salfity, 1989Marquillas et al 2003Marquillas et al , 2005Cónsole-Gonella et al 2012Cónsole-Gonella & Marquillas, 2014;Bunevich et al 2017;Gomes et al 2019;Deschamps et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The experience accumulated in many years of research and application by Petrobras School of High-Resolution Stratigraphy (e.g., Raja Gabaglia 1991, Bento Freire 2012, De Gasperi and Catuneanu 2014, Pedrinha et al 2015, Roemers-Oliveira et al 2015, Magalhães et al 2016, Bunevich et al 2017, Melo et al 2020, Gomes et al 2020, Magalhães et al 2020, Silveira 2020 reinforces the importance of the interdependence between description and interpretation for the development of sequence stratigraphy principles and practice.…”
Section: Final Remarksmentioning
confidence: 96%
“…4); Magalhães et al (2016), in estuarine strata of Tombador Formation (Fig. 21); Bento Freire (2012), Bunevich (2016), Bunevich et al (2017), and Gomes et al (2020), in lacustrine carbonate from Yacoraite Formation (Fig. 22); and Melo et al (2020), in a fluvial interval of Açu Formation (Fig.…”
Section: High-resolution Sequence Stratigraphymentioning
confidence: 99%
“…Marquillas et al, 2011;Rohais et al, 2019). They are known to be coeval with the Palmar Largo volcanism (70 to 60 Ma; Fernandez, 1975;M€ adel, 1984;G omez-Omil et al, 1987;Omarini et al, 1989;Disalvo et al, 2002), although they were also attributed to the Late Cretaceous volcanic arc of northern Chile (Marquillas et al, 2011) and have provided one of the oldest, recycled zircon grains of South America (3.7 Ga; Paquette et al, 2015).…”
Section: Geological Setting and Geochronological Backgroundmentioning
confidence: 99%